Towards Development of OER Derived Custom-Built Open Textbooks: A Baseline Survey of University Teachers at the University of the South Pacific - Prasad, Deepak; Usagawa, Tsuyoshi (International Review of Research in Open and Distributed Learning, 2014)
Textbook prices have soared over the years, with several studies revealing many university students are finding it difficult to afford textbooks. Fortunately, two innovations – open educational resources (OER) and open textbooks – hold the potential to increase textbook affordability. Experts, though, have stated the obvious: that students can save money through open textbooks only if teachers are willing to develop and use them. Considering both the high price of textbooks and the benefits offered by OER and open textbooks, the aim of this study was to assess the University of the South Pacific (USP) teachers’ willingness towards development of custom-built OER derived open textbooks for their courses with a focus on providing a foundation for strategies to promote open textbook development at USP. This paper reports the findings of an online survey of 39 USP teachers. The results show that 17 teachers were willing to develop OER derived custom-built open textbooks for their courses. Besides this, there are findings relating to six important areas: teachers’ motivation to develop open textbooks; the frequency of more than one prescribed textbook per course; teachers’ awareness of the costs of the prescribed textbooks; the average cost of prescribed textbooks in a course; teachers’ awareness and utilization of OER and open textbooks; and teachers’ perceived barriers to using OER and types of challenges they encounter while using OER. These findings have been discussed in relation to research studies on OER and open textbooks.